Thermal decomposition synthesis of nanorods bismuth sulphide from bismuth N-ethyl cyclohexyl dithiocarbamate complex - Abdullah, Nurul Hidayah; Zainal, Zulkarnain; Silong, Sidik; Mohamed Tahir, Mohamed Ibrahim; Kar, Ban Tan; Sook, Keng Chang (Elsevier BV, 2016)
Nanorods of bismuth sulphide were prepared by thermal decomposition of bismuth N-ethyl cyclohexyl dithiocarbamate at different calcination duration. X-ray diffraction (XRD) analysis shows that at 400 °C, the precursor was fully decomposed to orthorhombic bismuth sulphide after 2 h of calcination. Besides, calcination duration does not affect the existence of Bi2S3 phase. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analyses reveal that Bi2S3 nanorods with an average width ranging from 29–36 nm were obtained. Energy dispersive X-ray (EDX) analysis confirmed the atomic ratio of Bi and S close to 2:3, giving a possible composition of Bi2S3. Direct band gap energy of Bi2S3 decreases from 1.83 eV to 1.54 eV as calcination time increases.